An exploratory study toward understanding social entrepreneurial intention - Haque, A. K. M. Ahasanul; Naila, Naila Anwar; Yasmin, Farzana; Asadul Islam, Md Asadul Islam (RPA Journals, 2018)
Societies are struggling from an array of social complications. The presence of such complications can be observed in the form of poverty, education disparity, malnutrition, inadequate infrastructure and medical services, environmental hazards, just to name a few. The reduction of such complications has become a major concern for many countries in various regions across the world. Thus, today’s societies are in a great need of social entrepreneurs, as they have the ability to minimise such complications through the development of sustainable social enterprises. Hence, individuals’ intention of establishing a social venture has emerged as a more recent area of inquiry which calls for further exploration. With this thought, this paper has been crafted for acquiring in-depth insight regarding the development of social entrepreneurship through exploring the intentions of future social entrepreneurs and mapping how their intentions will be translated into reality. The findings suggest that intention to create a social venture is initiated thorough individuals personal experiences along with their concern toward helping humanity. Such intentions can be brought to light through the enhancement of certain skills, social support as well as overcoming the obstacles that may arise.